Stommontaget av ett demonstrationshus byggt i pelar-balk system i limträ - Tlustochowicz, Gabriela (Luleå, 2008)
Beam and post system has a number of advantages as simplicity and flexibility, and freedom in architectural design. This system, also called skeleton frame system has a long history in housing, but since the world is dominated by tendency optimization and economization the heavy solid timber structures for houses applies just for individual projects, mostly for aesthetical reasons. Since the beam and post system is effective and competitive for large spans, the system requires large dimensions of members. Glued laminated timber with higher strength parameters is more suitable for this system and that is why it became an object of interest of Moelven Töreboda AB.The company Moelven Töreboda AB took a first step towards wider use of beam and post system in timber housing by building a demonstration house with the use of glulam and Kerto LVL boards . The erection of the building was a subject to a detailed study during my presence on the building-site for a period of seven working weeks and the result of this work is presented in this report. The study method was observation and interviews, and the data was preserved in form of photographs and notes, and processed afterwards.The report is an introductory work to the research on optimization of a beam and post system in timber. The project is a result of cooperation between Luleå University of Technology and Moelven Töreboda AB. The long-perspective aim of the project is a development of an optimizing method for timber houses, which can be applied in the design stage. Pelar-balk system erbjuder fördelar såsom enkelhet och flexibilitet och lämnar stor frihet åt arkitekten. Systemet har en lång tradition i husbyggandets historia, men på grund av rådande tendens mot optimering och ekonomi, solida trästommar appliceras bara för individuella projekt av estetiska skäl. Eftersom pelar-balk system är effektivt och konkurrenskraftigt för stora spännvidder, kräver systemet stora dimensioner. Limträ med bättre hållfasthet parametrar är mer lämpligt för systemet och därför ...